Mosque - Macaulay, David (Boston : Houghton Mifflin, 2003)
Reveals the methods and materials used to construct a mosque in late-sixteenth century Turkey.
"Walter Lorraine books.".
Wilson's Children.
Wilson's Junior High School.
Wilson's Senior High School.
7.5
3-6
Keywords: Mosques -- Design and construction -- Juvenile literature; Mosques; Mosques; Turkey -- Civilization; Turkey -- Civilization